2012
DOI: 10.1179/1973947812y.0000000013
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous histology of colon cancer predicts poor outcomes with FOLFOX regimen in metastatic colon cancer

Abstract: Mucinous adenocarcinoma (MA) of colorectal cancer seems associated with reduced responsiveness to chemotherapy. The overexpression of markers of resistance to fluorouracil and oxaliplatin has recently been demonstrated. We revised the outcomes of metastatic MA of the colon treated with FOLFOX. From January 2002 to December 2009, we treated 198 patients with metastatic colon cancer, of which 21 (10.6%) had diagnosis of MA and were compared with 42 control patients with non-mucinous adenocarcinoma (NMA). In MA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…In our study, after stratified analyses and adjustment for tumor stage, age at diagnosis, gender and tumor site, MAC was found to be an independent predictor of poor prognosis. This finding is consistent with several previous studies, including three retrospective studies in CRC patients treated with first-line chemotherapy, showing that patients with mucinous histology had much worse prognoses than those with the non-mucinous subtype [ 31 , 34 37 ]. However, in some studies [ 2 , 7 , 18 , 38 ], after subgroup analysis and multivariate analysis, MAC was not an independent adverse prognostic factor, but instead was related to tumor stage or specific tumor site.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, after stratified analyses and adjustment for tumor stage, age at diagnosis, gender and tumor site, MAC was found to be an independent predictor of poor prognosis. This finding is consistent with several previous studies, including three retrospective studies in CRC patients treated with first-line chemotherapy, showing that patients with mucinous histology had much worse prognoses than those with the non-mucinous subtype [ 31 , 34 37 ]. However, in some studies [ 2 , 7 , 18 , 38 ], after subgroup analysis and multivariate analysis, MAC was not an independent adverse prognostic factor, but instead was related to tumor stage or specific tumor site.…”
Section: Discussionsupporting
confidence: 93%
“…One study included stage II and III CRC patients who were treated with adjuvant FOLFOX chemotherapy. It showed that only MAC had an adverse prognostic impact whereas PMAC patients had better disease-free survival (DFS), similar to that for CRC patients without any mucin [ 31 ]. Multivariate analysis revealed MAC, not PMAC, to be an independent negative prognostic factor of DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic versus rectal location also exhibited a different pattern by race and age respectively: <61 yrs (AA 70%, EA 50% colon); >= 61 (AA 70%, EA 80% colon). Mucinous histology and proximal location in the context of advanced stage cancer have been consistently associated with poorer CRC outcomes 4850 . In our investigation, we observed that mucinous histology (HR 1.44) and--to a lesser extent --colonic location (HR 1.97) attenuated the association between race and survival among the younger persons.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, one would expect a worse response to chemotherapy in mucinous cancers, as they contain a higher rate of microsatellite instable tumors and B-Raf proto-oncogene, serine/threonine kinase mutations (but also phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha and transforming growth factor beta mutations [21]) compared to nonmucinous tumors [22], which previously have been demonstrated to be linked to a worse prognosis. However, most of the studies investigating efficacy of chemotherapeutic treatment in mucinous CRC were rather small [23-25] and by far not sufficient for obtaining reliable data. Our data point toward a similar efficacy of adjuvant and palliative chemotherapy in mucinous and adenocarcinoma CRC and do not support the conclusions drawn in earlier and smaller studies.…”
Section: Discussionmentioning
confidence: 99%